2020
DOI: 10.1126/sciadv.aay5981
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of known ssRNA phage genomes: From tens to over a thousand

Abstract: The first sequenced genome was that of the 3569-nucleotide single-stranded RNA (ssRNA) bacteriophage MS2. Despite the recent accumulation of vast amounts of DNA and RNA sequence data, only 12 representative ssRNA phage genome sequences are available from the NCBI Genome database (June 2019). The difficulty in detecting RNA phages in metagenomic datasets raises questions as to their abundance, taxonomic structure, and ecological importance. In this study, we iteratively applied profile hidden Markov models to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
160
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(164 citation statements)
references
References 71 publications
4
160
0
Order By: Relevance
“…This hints to different factors shaping the mat layers microbial composition, such as bacterial predation by nematodes [122] or seasonal variation in bacterial/archaeal metabolism [123]. While our work shed light on diversity of dsDNA and ssDNA viruses in microbial mats, further work might involve investigation of ssRNA viruses, as these have been found in abundance in other environments [124,125] and could play a role in biofilm formation [54]. We believe that our observations can be expanded to other natural biofilms and contribute to the development of novel microbial dynamics prediction models for biofilms.…”
Section: Discussionmentioning
confidence: 79%
“…This hints to different factors shaping the mat layers microbial composition, such as bacterial predation by nematodes [122] or seasonal variation in bacterial/archaeal metabolism [123]. While our work shed light on diversity of dsDNA and ssDNA viruses in microbial mats, further work might involve investigation of ssRNA viruses, as these have been found in abundance in other environments [124,125] and could play a role in biofilm formation [54]. We believe that our observations can be expanded to other natural biofilms and contribute to the development of novel microbial dynamics prediction models for biofilms.…”
Section: Discussionmentioning
confidence: 79%
“…Environmental studies have indicated that the family Microviridae contains at least five unclassified subfamilies [40][41][42][43][44][45][46][47]. Recently, Callanan et al [48] predicted 331 species and 247 genera among the single-stranded RNA phages, potentially leading to a significant expansion of the family Leviviridae.…”
Section: Future Directionsmentioning
confidence: 99%
“…The high diversity of the invertebrate RNA virome suggests that RNA viruses of land plants and vertebrates evolved from viruses infecting invertebrates 2 . The known RNA viromes of plants, fungi, protists and bacteria have also expanded through meta-transcriptome sequencing, albeit not as massively as the invertebrate virome 19,[34][35][36][37][38][39][40][41] .…”
mentioning
confidence: 99%